RELATIONSHIP BETWEEN ROOM HEAD SUPERVISION AND NURSES COMPLIANCE IN IMPLEMENTING FALL RISK PREVENTION IN THE INPATIENT ROOM OF ARIFIN ACHMAD HOSPITAL - Hikmah, Muttakhidatul; Suci, Wice Purwani; Dwi Guna, Stephanie (Universitas Airlangga, 2025)
Introduction: The purpose of this research was to determine the relationship between room head supervision and nurses’ compliance in implementing fall risk prevention in the inpatient room at Arifin Achmad Hospital. Methods: This research used a descriptive correlative design with a cross-sectional approach. The research sample consisted of 76 respondents, selected using the total sampling technique. Supervision was measured using a 28-item questionnaire, consisting of 17 favorable items and 11 unfavorable items, with a Cronbach’s alpha reliability coefficient of 0.912. Nurse compliance was measured using a 9-item questionnaire, with a Cronbach’s alpha reliability coefficient of 0.973. Data were analyzed using bivariate analysis with the chi-square test. Results: The results of the study showed that 39 nurses (51.3%) were in the compliant category in implementing fall risk prevention. Most of the compliant nurses received good supervision from the head room, as reported by 29 nurses (72.5%). Meanwhile, among the 37 nurses (48.7%) in the less compliant category, the majority received poor supervision from the head room, as stated by 26 nurses (72.2%). The statistical test results showed a p-value of 0.000 (< 0.05), indicating that the null hypothesis (H₀) was rejected. Conclusions: It can be concluded that there is a significant relationship between head room supervision and nurses’ compliance in implementing fall risk prevention in the inpatient rooms of Arifin Achmad Hospital.